Effect of Water Soluble Polymers on Dissolution Enhancement of Ibuprofen Solid Dispersion Prepared by Fusion Method (Stamford Journal of Pharmaceutical Sciences, 2011)
The purpose of this study was to prepare and characterize solid dispersions of the NSAID Ibuprofen with PEG 6000, Poloxomer 188 and Poloxomer 407 with the intention of improving its dissolution properties. The solid dispersions were prepared by the fusion method. Evaluation of the properties of the dispersions was performed using dissolution studies. The results obtained showed that the rate of dissolution of Ibuprofen was considerably improved when formulated in solid dispersions with PEG 6000 and poloxomer 188. Solid dispersions with poloxomer 407 showed drug retarding capability which may trigger more research in the intension of exploiting this feature to prepare sustained release dosage form. Key words: Ibuprofen; polyethylene glycol; poloxomer; solid dispersion; fusion method; dissolution DOI: 10.3329/sjps.v3i1.6801S. J. Pharm. Sci. 3(1): 63-67